GE_GERICHTE P/26186/2023 vom 9. August 2024 - GE Cour de justice (2024)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;VIOLATION DE DOMICILE;AVOCAT;HONORAIRES | CPP.310.al1.leta; CP.186; CPP.429.al1.leta; CPP.429.al2